Separation of dynamic and isostatic components of the Venusian gravity and topography and determination of the crustal thickness of Venus. (15th September 2016) - Yang, An; Huang, Jinshui; Wei, Daiyun
Abstract: Assuming that the long-wavelength geoid and topography of Venus are supported by both mantle convection and Airy isostasy, we propose a method to separate the dynamic and isostatic components of the Venusian gravity and topography with the aid of the dynamic admittance from numerical models of mantle convection and the isostatic admittance from an Airy isostatic model. The global crustal thickness is then calculated based on the isostatic component of the gravity and topography. The results show that some highland plateaus such as Ishtar Terra and Ovda Regio have thick crust, which are largely supported by isostatic compensation. Other highland plateaus such as Thetis and Phoebe Regiones appear to have superimposed contributions from crustal thickening and dynamic support. Volcanic rises such as Atla and Beta Regiones have thin crust, which is consistent with the postulation that these volcanic rises are mainly the products of dynamic uplift caused by mantle plumes. Highlights: We propose a method to separate the dynamic component of Venusian gravity and topography. Results show a combined dynamic and isostatic compensation for highland plateaus Results show mainly dynamic compensation for volcanic rises. The global crustal thickness of Venus has been inverted.